2002
DOI: 10.1046/j.1464-410x.2002.02785.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the chronic use of finasteride on testicular weight and spermatogenesis in Wistar rats

Abstract: Objective To evaluate spermatogenesis in rats chronically exposed to finasteride, as the recent use of finasteride in young men to prevent hair loss has raised concerns about chronic use and fertility. Materials and methods Male Wistar rats (4 months old)were selected and divided into two groups. Group 1 (17 rats) received a finasteride suspension of 2 mg/kg/ day in saline solution, 5 days/week for 10 months; group 2 (eight rats of the same age) were treated with placebo for the same period. At the end of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 9 publications
(23 reference statements)
0
12
1
Order By: Relevance
“…According to these results, it was shown in male rats during puberty that a peak of 5-a reductases and 5-a-reduced metabolites coincided with the first wave of spermatogenesis, suggesting a role for 5-a reductases in the initiation of spermatogenesis (Killian et al 2003). In studies during adulthood, no effects of FIN on testicular histomorphology were found in rats (George et al 1989, Rhoden et al 2002 and dogs (Juniewicz et al 1993). By contrast, a study performed in adult rats showed that administration of FIN suppressed the testosterone-induced restoration of spermatogenesis and demonstrated clearly a role for 5-a-reduced androgens in adult spermatogenesis (O'Donnell et al 1996).…”
Section: Discussionmentioning
confidence: 90%
“…According to these results, it was shown in male rats during puberty that a peak of 5-a reductases and 5-a-reduced metabolites coincided with the first wave of spermatogenesis, suggesting a role for 5-a reductases in the initiation of spermatogenesis (Killian et al 2003). In studies during adulthood, no effects of FIN on testicular histomorphology were found in rats (George et al 1989, Rhoden et al 2002 and dogs (Juniewicz et al 1993). By contrast, a study performed in adult rats showed that administration of FIN suppressed the testosterone-induced restoration of spermatogenesis and demonstrated clearly a role for 5-a-reduced androgens in adult spermatogenesis (O'Donnell et al 1996).…”
Section: Discussionmentioning
confidence: 90%
“…Overstreet et al 10 investigating humans and Rhoden et al 11 investigating rats, did not show any alterations in the spermatogenesis after treatment with finasteride. Overstreet et al 10 evaluated the ejaculate from young men under use of finasteride 1mg and compared them to a control group.…”
Section: Discussionmentioning
confidence: 93%
“…However, this effect was felt to be secondary to inadequate copulatory plug formation, secondary to the drug's effects on seminal vesicles and the prostate (4,5). Further studies did not show an effect on spermatogenesis (6). Therefore, the effects of finasteride on fertility seen in rats were felt to be a species specific.…”
Section: Discussionmentioning
confidence: 99%